Relative distribution, diversity, and bloodmeal sources of mosquitoes and known vectors of Rift Valley fever phlebovirus in three differing ecosystems in Bura, Tana River County, Kenya - Mbotha, Deborah; Hoppenheit, A.; Lindahl, Johanna F.; Bett, Bernard K.; Grace, Delia; Lutomiah, J.; Pieper, L.; Kairu-Wanyoike, Salome; Clausen, Peter-Henning (Mary Ann Liebert Inc, 2020)
Environmental modifications disturb the equilibrium of mosquito populations, altering the risk of mosquito-borne diseases. Mosquito distribution, diversity, and bloodmeal sources were examined to compare Rift Valley fever (RVF) risk among irrigated, riverine, and pastoral ecosystems in Bura, Tana River County, Kenya, between September 2014 and June 2015. Thirty-eight households and 21 irrigation fields were selected for the study. Mosquitoes were trapped with carbon dioxide-impregnated CDC traps, one trap per household and three traps per irrigated field, and morphologically identified using taxonomic keys. Host DNA was extracted from engorged females and cytochrome b genes amplified by PCR to identify sources of bloodmeals. A total of 21,015 mosquitoes were collected; 5742 within households in the 3 ecosystems and 15,273 within irrigated fields. Mosquitoes collected within irrigated fields belonged to 8 genera and 37 species, while those from households within the irrigation scheme belonged to 6 genera and 29 species. Collections from riverine and pastoral households belonged to five and four genera, respectively. The most abundant genera in the irrigated fields were Aedes (21%) and Mansonia (22%), while Anopheles (43%) was the most abundant within households. Most mosquitoes in riverine and pastoral households belonged to Anopheles (76%) and Aedes (65%) genera, respectively. Seasonal variation driven by rainfall was evidenced by spikes in mosquito numbers within irrigated and riverine ecosystems. Host species identification revealed that goats and humans were the main sources of bloodmeal. There was an overall increase in mosquito abundance and diversity as a result of the presence of the irrigated ecosystem in this county, and an increased availability of highly RVF-susceptible hosts as a result of the establishment and concentration of residential areas, promoting potential vector–host contacts. These results highlight the impact of anthropogenic changes on mosquito ecology, potentially heightening the risk of transmission and maintenance of RVF in this region.